EFEKTIVITAS METODE PEMBELAJARAN E-LEARNING TERHADAP KEMANDIRIAN BELAJAR MAHASISWA PADA MATA KULIAH BAHASA INDONESIA - Desma Yuliadi Saputra; Rina Andriani (LPPM Universitas Bina Bangsa, 2024)
The rapid advancement of technology has significantly impacted the diversity of learning methods. One increasingly adopted method is e-learning, which allows students to access learning materials anytime and anywhere. This method provides various learning media that serve as facilitators in online learning. The use of e-learning has both positive and negative implications, such as enhancing students' learning independence while also potentially fostering dependence on the internet. This study aims to identify the influence of e-learning learning methods on students' learning independence. The research employs a descriptive quantitative approach using a survey method with questionnaires. The study involved 52 students enrolled in the Indonesian Language course using the e-learning learning method. The results indicate that the use of e-learning in the Indonesian Language course significantly affects students' understanding of e-learning utilization and application, with a percentage of 50%. Furthermore, the findings suggest that e-learning contributes to students' learning independence, as it encourages them to actively seek learning resources on their own